Practice-oriented technologies as a means of forming students' communicative competence - Tatarnitseva, Svetlana N. (2020)
One of the most important features of professional activity is the ability to build a dialogue, organize business communication. The possession of communicative competencies provides the student with the opportunity to quickly achieve their goals through the implementation of speech turnovers and constructions that comply with the principles and standards of speech etiquette, affecting the establishment and maintenance of the psychological climate in the process of interaction. The purpose of the article is to review the experience of forming communicative competencies with the help of practice-oriented technologies. Requirements for the formation of communicative competencies are reflected in regulatory documents. The competencies under consideration represent the student's ability to build productive professional interaction using various communication methods. We reveal the motivational, cognitive, and active components of communicative competencies, reflecting the desire for interpersonal communication and support for established interaction, the student's understanding of the value of communicative competencies in future professional activities, and the ability to organize effective cooperation. Practice-oriented technologies, including case studies and design, contribute to solving professional problems through group discussions and situation analysis. The study revealed the impact of practice-oriented technologies implemented in higher education institutions on the formation of students' communicative competence.